STRATEGI KOPING PADA PELANGGAR QANUN JINAYAH DITINJAU DARI JENIS KELAMIN - Affan Maulana Ghiffari; Haiyun Nisa (Journal of Research and Measurement in Psychology, 2019)
Qanun Jinayah violators who are serve a period of detention experience various psychological problems such as depression, anxiety, phobias, and anti-social personality. To be able deal with these various problems, Qanun Jinayat violators need a coping strategy. The purpose of this study was to determine the differences of coping strategies in Qanun Jinayat violators in terms of gender. The sample in this study consisted of 13 male and 13 female who violated Qanun Jinayat in several prison in Aceh province. To identify coping strategies used by Jinayat lawbreakers, researcher used the WCCL-ASIAN scale with results of data analysis showed p = 0,588 for problem focused coping strategies, the results of data analysis showed p = 0,551 for seek social support coping strategies, the results of data analysis showed p = 0,231 for blame self coping strategies, the results of data analysis showed p = 0,300 for wishful thinking coping strategies, and results data analysis shows p = 0,036 for avoidance coping strategies. The results showed that there were no differences in problem focused, seek social support, blame self, and wishful thinking coping strategies, but there are difference in avoidance coping strategies for Qanun Jinayah violators, both male and female.